The dragon well - Willis, Daniel, 1957-; Rams, Vinod (Renton, WA : Mirror Stone/Wizards of the Coast ; [New York] : Distributed in the U.S. by Holtzbrinck, 2004)
The mission of Nearra and her companions turns into a disaster and they will never be the same again.
Ages 10-up.
Accelerated Reader AR
Keywords: Quests (Expeditions) -- Juvenile fiction; Krynn (Imaginary place) -- Juvenile fiction; Good and evil -- Juvenile fiction; Quests (Expeditions) -- Fiction; Krynn (Imaginary place) -- Fiction; Good and evil -- Fiction; Fantasy; Fantasy fiction